Dammarane-type triterpenoid saponins from Salvia russellii Benth. (April 2021) - Hafez Ghoran, Salar; Firuzi, Omidreza; Asadollahi, Mojtaba; Stuppner, Hermann; Alilou, Mostafa; Jassbi, Amir Reza
Abstract: Three undescribed dammarane-type saponins, russelliinosides A-C, together with a common sterol (β-sitosterol), an abietane diterpenoid (18-hydroxyferruginol), two oleane triterpenoids (daturaolone and oleanolic acid), an ursane triterpenoid (ursolic acid) as well as three 5-hydroxyflavones (cirsimaritin, eupatorin, and salvigenin) were isolated from a dichloromethane extract of the aerial parts of Salvia russellii Benth. The chemical structures of the aforementioned compounds were characterized, using detailed spectroscopic analyses, including high-resolution mass spectrometry and 1D and 2D NMR ( 1 H– 1 H COSY, TOCSY, HSQC, HMBC and NOESY) spectroscopy as well as physicochemical properties. Cytotoxic effects of S. russellii extract and the three isolated russelliinosides were tested against MCF-7 human breast and A549 lung cancer, as well as non-cancer NIH/3T3 cells using MTT reduction assay. Russelliinosides A and B exhibited cytotoxic activities with IC50 values of 7.1 and 30.7 μg/ml against MCF-7 and 33.9 and 69.4 μg/ml against A549 cells, respectively, while russelliinoside C did not show cytotoxicity against cancer cells. On the other hand, russelliinoside A showed an IC50 value of 31.5 μg/ml against NIH/3T3 cells, while russelliinosides B and C had no effect on the viability of these non-cancer cells. Graphical abstract: Image 1 Highlights: Three cytotoxic dammarane triterpene saponins were isolated from Salvia russellii. Three 5-hydoxyl-polymethoxy flavones, β-sitosterol ursolic and oleanolic acid were isolated from S. russellii. Chemical structures of the undescribed compounds were elucidated by 1D, 2D-NMR, and HRESI-MS analyses.